Tensor complementarity problems: the GUS-property and an algorithm. Issue 9 (2nd September 2018) - Liu, Dongdong; Li, Wen; Vong, Seak-Weng
Abstract: In this paper, we study the global uniqueness and solvability (GUS-property) of tensor complementarity problems (TCPs) for some special structured tensors. The modulus equation for TCPs is also proposed, and based on this equation, we develop the corresponding nonsmooth Newton's method, which extends the existing method given in the work of Zheng H and Li W. The modulus-based nonsmooth Newton's method for solving linear complementarity problems. J Comput Appl Math. 2015;288: 116-126. Numerical examples are given to demonstrate the efficiency of the proposed algorithm.